Comércio internacional, pobreza e desigualdade de renda : uma análise para os municípios brasileiros de 2000 a 2010 - Gauterio, Laura Wichrowski (2015)
This work aims to analyze the effects of integration into world markets on household income inequality and poverty in brazilian municipalities from 2000 to 2010. The study employs a methodological approach developed by Castilho et al. (2012), based on a fixed effects model for panel data, and it has as main database the Demographic Census microdata from the Brazilian Census Bureau (IBGE). The estimated results for the set of brazilian municipalities suggest that poverty was reduced with an increase in exports and income inequality fell with increases in both exports and imports. In urban areas, the reduction in tariffs contributed to a decline in income inequality and a relative increase in poverty. In rural areas, the estimated effect is opposite to that provided to urban areas. By investigating the effect of trade integration in income distribution of each of the five brazilian regions, it appears that the largest trade exposure, in terms of lower tariffs, have a negative effect on poverty only in regions with highest poverty rates. The results for income inequality remained identical to those found for the country in all regions. Regarding trade flows, the estimated results confirm the reduction in income inequality with an increase in exports in all regions. The increase in imports would have contributed to income concentration in poorest regions and to its reduce in wealthier regions. Regarding the effects of trade on poverty, it appears to have no pattern that can be provided based on trade and distributive patterns of regions.